The Protection Effect of Mango (Mangifera indica L.) Fruit Juice on Renal Histological Structure of Mice Induced Paracetamol - Wirawan, Wahyu; ., Muthmainah; Dharmawan, Ruben (Nexus Kedokteran Translasional, 2013)
Background: Mangifera indica L. fruit contains vitamin C, vitamin E and Î²-carotene which are thought to protect the ren from free radicals. In present study, Mangifera indica L. fruit is evaluated for its protection effect on paracetamol induced renal cell damage in mice. Methods: To evaluate the nefroprotective effect of Mangifera indica L. fruit juice, 28 male Swiss webster mice were equally divided into four groups. Mice in group I (KKn) were given aquadest and group II (KKp) received paracetamol for 3 days. Group III-IV (KP1 and KP2) not only received paracetamol, but also received multilevel doses of Mangifera indica L. fruit juice for 14 days. Mice were sacrificed on the 15th day and histological preparation was made to evaluate histological damage in ren. Renal histological structures wereÂ  assessedÂ  byÂ  countingÂ  theÂ  numberÂ  of renal cells on proximal tubule undergoing pyknosis, karyorhexis, and karyolysis. Data were analyzed using the One Way ANOVA test (Î± = 0.05) and the Post Hoc Multiple Comparisons (LSD) test (Î± = 0.05). Results: The mean renal cell histological damage score in KKp group : 36.43 Â± 1.66, KKn group : 6.5 Â± 1.34, KP1 group : 14.86 Â± 1.56, KP2 group : 8.5 Â± 2.13. The results of One Way ANOVA test showed significant difference between the four groups (p=0.000) and the results of LSD test showed significant differences between each other group (p<0.005). Conclusions: Mango fruit juice can decrease the damage of renal histological structure in mice induced by paracetamol, and increasing the dose of mango fruit juice can increase its protection effect on histological structure of renal cell therefore it canât give the same histological structure as in control group. Keywords: Mangifera indica L. fruit juice, paracetamol, renal cell histological damage.